Detection of real-time patterns in sports: Interactions in soccer - Anguera-Argilaga, M. T.; Jonsson G.K. (International Journal of Computer Science in Sport, 2002)
In the pursuit of generating quantitative information on performance sport researchers have traditionally used frequency of event occurrence as their index of performance (Borrie, Jonsson & Magnusson, 2002). However, frequency of event occurrence has been shown to be an inadequate index of performance that cannot differentiate between effective performances (Borrie & Jones, 1998). If performance analysis is to continue to advance understanding of sports performance then it must find better methods of collecting and analyzing match analysis data. The analysis approach used here is based on a process known as T-pattem detection which allows the detection of the temporal and sequential structure of data sets. The method has been developed on the assumption that complex streams of human behaviour have a temporal/sequential structure than cannot be fully detected through unaided observation or with the help of standard statistical and behaviour analysis methods. Given that observational records of human behaviour have both a temporal and sequential structure an analysis tool that can describe this structure will enhance understanding of the behaviour (s) being studied. A generic observational software package called Theme has been specifically developed to operationalise T-pattem detection as an analysis process (Magnusson, 1996, 2000).